Culture Shock Experienced by Students from Maluku at Makassar - Marasabessy, Jasna (English Literature Studi Program Universitas Islam Makassar, 2024)
Culture shock is a condition where individuals feel shocked, confused, anxious, and restless when moving from their home area to a culturally distinct environment. This phenomenon can cause challenges in intercultural communication. This study explores the factors and impacts of culture shock experienced by students from Maluku studying in Makassar. Using a qualitative descriptive approach, the study draws on primary and secondary data from five student informants through interviews, observations, and documentation. Key findings reveal that language, food, and environmental factors contribute to culture shock, while impacts are categorized into positive (e.g., adaptation, cultural learning) and negative (e.g., anxiety, loss of appetite) outcomes. These findings imply that students need better preparation for transitioning into new cultural contexts.